1988
DOI: 10.1080/00288233.1988.10423421
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in the dimensions of individual Romney wool fibres determined by a rapid autoradiographic technique

Abstract: A technique for radio-labelling short regions of growing wool fibres was modified by using intradermal injections of 3H-cystine and a rapid detection method. This technique allowed emergence times and dimensional changes of individual wool fibres to be rapidly and precisely monitored. Seasonal changes in fibre dimensions were determined for five sheep on maintenance nutritional levels following monthly injections over 12 months. Fibre diameter and length-growth varied seasonally, maximum and mimimum values occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 16 publications
1
7
1
Order By: Relevance
“…At the break of season, liveweight and wool production changes were closely matched and within the time frame for responses recorded from a base diet with protein and amino acid supplementation regimes (Reis et al 1973;Reis and Tunks 1978;Hynd and Allden 1985). Grazing Merino wethers had a large and statistically significant variation in L : D ratio, in line with that recorded for Romney sheep (Woods and Orwin 1988). Purser (1980) suggested that L : D ratio varied over the year for Merino sheep grazing in a Mediterranean environment, based on divergences in the relationship between clean wool growth and fibre diameter.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…At the break of season, liveweight and wool production changes were closely matched and within the time frame for responses recorded from a base diet with protein and amino acid supplementation regimes (Reis et al 1973;Reis and Tunks 1978;Hynd and Allden 1985). Grazing Merino wethers had a large and statistically significant variation in L : D ratio, in line with that recorded for Romney sheep (Woods and Orwin 1988). Purser (1980) suggested that L : D ratio varied over the year for Merino sheep grazing in a Mediterranean environment, based on divergences in the relationship between clean wool growth and fibre diameter.…”
Section: Discussionsupporting
confidence: 64%
“…Black (1987), in an analysis of unpublished data of D. J. Cottle, similarly found L : D ratio varied with nutritional status that altered wool growth but found that L : D 2 was constant. In both this grazing study and Woods and Orwin (1988) L : D 2 had significant variation with time when sheep were exposed to the full seasonal grazing environment.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The amplitude is less pronounced in modern Merino sheep than in Angora goats and most other sheep breeds (Margolena, 1974;Ryder, 1978). The seasonal cycle in fibre growth is associated with concomitant changes in fibre length, growth rate, mean fibre diameter and mean fibre volume (Woods and Orwin, 1988). This seasonal cycle of fibre growth, and occasional fleece shedding, in modern SC breeds, therefore appears to be a vestige of the moulting cycle of primitive and DC breeds (Ryder, 1978).…”
Section: Fibre Growth Patternmentioning
confidence: 99%